TINJAUAN YURIDIS TERHADAP TUGAS DAN FUNGSI BALAI PEMASYARAKATAN KLAS II A PEKANBARU DALAM RANGKA PENCAPAIAN TUJUAN PEMIDANAAN TINDAK PIDANA NARKOTIKA - Debi Jelitman Dakhi; Firdaus '; Erdianto ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Along with the times today, more and more phenomena that we face in everyday life of the community. Among these phenomena as phenomena in the economic, social and cultural sectors, politics, and law. This type of research can be classified sociological law research. This study explains that: First, the duties and functions of correctional Hall Class II A Pekanbaru in the achievement of the objective of sentencing narcotic crime. Secondly, efforts should be made by the Central Penitentiary Class II A Pekanbaru in the achievement of the objective of sentencing narcotic crime. From the research results can be concluded that the Correctional Centres Whereas Class II A Pekanbaru already perform the duties and functions optimally, but there are constraints faced by the Central Penitentiary Class II A Pekanbaru in guiding inmates. This is evident from a report in 2016 which showed that there were inmates who return to crime (recidivism), especially in narcotic crime. The efforts made by the Central Penitentiary Class II A Pekanbaru in carrying out the duties and function of conducting individual counseling and group counseling. Where in the guidance of the inmates were given skills training in order to provide supplies to inmates. So that when inmates were out of BAPAS, inmates have the ability or skill and can work according to skills possessed. To meet the needs of the convict life and can be re-active in the development of society.Keywords: Judicial Review -Task -Function - Interest Punishment.